1993
DOI: 10.1037/0096-1523.19.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effect of attention on simple visual search.

Abstract: Set-size effects in visual search may be due to 1 or more of 3 factors: sensory processes such as lateral masking between stimuli, attentional processes limiting the perception of individual stimuli, or attentional processes affecting the decision rules for combining information from multiple stimuli. These possibilities were evaluated in tasks such as searching for a longer line among shorter lines. To evaluate sensory contributions, display set-size effects were compared with cuing conditions that held senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
416
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(448 citation statements)
references
References 73 publications
28
416
0
Order By: Relevance
“…Furthermore, one can normalize the threshold ratio by the ratio of set sizes. In particular, Palmer et al (1993) borrowed a measure from studies of light adaptation. The log-log slope is the log of the threshold ratio relative to the log of the set-size ratio.…”
Section: Two Approaches To Measuring Set-size Effectsmentioning
confidence: 99%
“…Furthermore, one can normalize the threshold ratio by the ratio of set sizes. In particular, Palmer et al (1993) borrowed a measure from studies of light adaptation. The log-log slope is the log of the threshold ratio relative to the log of the set-size ratio.…”
Section: Two Approaches To Measuring Set-size Effectsmentioning
confidence: 99%
“…It can be shown that detection of small probe stimuli is enhanced on and immediately around the attended object [33]. One can even mimic a set size variation by simply telling observers which items to attend to on any given trial [34]. It may be that spatially selective attention serves a useful role in collecting features from just one object at a time and delivering those features to later object recognition processes [35].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…For an ideal observer with no capacity limitation (Palmer et al, 1993), this procedure eliminates statistical uncertainty. However, cuing cannot eliminate capacity limitations in the observer.…”
Section: Statistical Uncertainty Effect Versus Capacity Limitationmentioning
confidence: 99%
“…Statistical uncertainty reflects information loss and decision limits of the observer, not changes of perceptual sensitivity or limits of information-processing capacity of the ideal observer. Statistical uncertainty effects must be considered before drawing any conclusions about attention effects (Palmer, Ames, & Lindsey, 1993;Shaw, 1984;Sperling & Dosher, 1986).…”
Section: Statistical Uncertainty Effect Versus Capacity Limitationmentioning
confidence: 99%